Experimental investigation on mechanical properties of FeCoCrNiMo High Entropy Alloy & B4C reinforced Al6061 hybrid MMCs. (2021) - Chitturi, Suresh; Bhaumik, Munmun; Dandu, Kesava; Mudidana, Ravi Kiran
Abstract: Metal matrix composites are the new innovating materials used in daily life for quite some time. In the current research work Al6061 is used as matrix material and FeCoCrNiMo High Entropy Alloy (HEA) and Boron Carbide (B4 C) used as reinforcements. An attempt has been taken to fabricate hybrid MMCs considering aforementioned matrix and reinforcements through manual stir casting method by varying the volumetric concentrations (1%, 2% & 3%) of reinforcements. After fabrication, combined effects of HEA and B4 C reinforcements on mechanical properties (tensile strength, hardness and impact strength) of MMCs have been studied. The results indicate that hybrid composite samples show superior mechanical properties compared to pure Al6061. Mechanical properties are improved with increased vol% of FeCoCrNiMo High Entropy Alloy. The maximum 29%, 11.8% & 25.3% improvement in ultimate tensile strength, toughness & hardness were observed with Al6061 + 3%HEA + 1%B4 C hybrid composite sample compared to pure Al6061.